Community Insights: Citizen Participation in Kamaishi Unosumai Decade-Long Recovery from the Great East Japan Earthquake - Nombulelo Kitsepile Ngulube; Hirokazu Tatano; Subhajyoti Samaddar (International Journal of Disaster Risk Science, 2023)
Abstract Numerous scholars and researchers have long advocated for citizen engagement in post-disaster recovery and reconstruction initiatives, although unique opportunities and challenges in effectively implementing citizen engagement still exist. It has been 12 years since the Great East Japan Earthquake, where the government called for a citizen-centered recovery and reconstruction process, and reconstruction in most areas in the Tohoku region has almost been concluded. Using qualitative data acquired through interviews with the residents, field observations during the World Bosai Walk, and questionnaire and archival research, this study aimed to discuss the overall reconstruction of Unosumai in Iwate Prefecture, giving the residents’ perspective on the benefits and challenges they faced in participating in recovery planning and reconstruction and how the community has been able to strengthen their participation in disaster reduction initiatives since the earthquake and tsunami. This discussion is crucial as it would effectively offer lessons on engaging residents in post-disaster recovery and reconstruction after mega-disasters.